Climate-related risks and coastal livelihoods: lived realities, gender and adaptation - Benya, Anele (Department of Environmental and Geographical Science, 2025)
Rural coastal people are highly susceptible to climate-related risks, which can result in a range of adverse impacts. These impacts are felt differently based on the assets people possess and their gender. This research seeks to understand how people in Tshani Mankosi, a coastal rural village in the Eastern Cape, South Africa, navigate the complex challenges presented by a changing climate onto their livelihoods. This research examines the nexuses between natural resource dependency, livelihoods and gender within the broader socio-economic and political landscape of South Africa. A qualitative research design was employed, particularly a case study approach, which allowed for an in-depth, context-specific exploration of the experiences and lived realities of the people of Tshani Mankosi within the broader socio-ecological, economic and gendered context. Empirical evidence was collected using semi-structured interviews, focus groups and direct observations of community life. In analysing the data, this study critically draws from the sustainable livelihoods framework (SLF), Dorward's livelihood aspirations theory and the concept of social reproduction, all with a gender lens. This mini dissertation argues that climate responses are influenced by how people understand and experience their natural environment and the assets they possess to reduce their vulnerability and increase adaptive capacity, ultimately leading to better livelihood outcomes. Key findings reveal that the respondents are aware of the changing climatic conditions, such as erratic rainfall, increased frequency of storm surges and winds, and longer high tide periods. The respondents noted minimal changes in their ocean-based livelihoods compared to their land-based livelihoods. While the respondents noted these changes, they attributed them to varying factors influenced by their positionality and beliefs. The study shows that climate change exacerbates existing vulnerabilities within this community, ultimately affecting people's adaptive capacity. While adaptation strategies such as diversification of livelihoods and drawing from local knowledge to enhance resilience, these efforts are often constrained by resource access, marginal government and institutional support, and gendered vulnerabilities. The findings also reveal how, in Tshani Mankosi, people have noted the increasing unreliability of local knowledge due to changing climatic conditions.